Application of Statistical Methods in Determining Learning Evaluation Values and Scores - Tri Haryati; Isti Koma; Alfira Mersania Shintia; Julmi Julmi (JISEI: Journal of Islamic Studies and Educational Innovation, 2025)
Learning assessment is an important aspect of education that requires accuracy, objectivity, and fairness, as assessments that rely solely on teacher subjectivity can lead to misinterpretation of students' abilities. This study aims to analyze the application of statistical methods in determining scores and evaluating results in learning. The method used is a literature review. The analysis was conducted based on literature related to statistical methods, including mean calculation, standard deviation, z-score, Pearson Product Moment correlation, Cronbach's Alpha, and multiple linear regression. The results indicate that applying statistical methods can improve the accuracy, validity, and reliability of evaluations, help teachers understand the distribution of student scores, determine achievement categories regularly, and reduce subjectivity in assessment. Therefore, the use of these methods allows for more objective and measurable assessments, serving as a basis for informed educational decision-making. Teachers and educational institutions are encouraged to regularly apply statistical methods to enhance learning quality and provide more meaningful feedback to students